Effect of reagents addition method in Fenton oxidation on the destruction of organics in palm oil mill effluent. Issue 4 (August 2020) - Gamaralalage, Disni; Sawai, Osamu; Nunoura, Teppei
Abstract: H2 O2 and Fe 2+ are the reagents added in Fenton oxidation and their rapid consumption affects the oxidation performances. In this study, effect of reagents addition methods on the oxidation performances in Fenton process was studied considering the palm oil mill effluent (POME) degradation. POME is a thick, acidic, brownish and odorous wastewater containing high organics and nitrogen which generates during crude palm oil production process. Seven reagents addition methods as "conventional", "continuous H2 O2 ", "fractional H2 O2 ", "continuous Fe 2+ ", "fractional Fe 2+ ", "continuous Fe 2+ and H2 O2 ", "fractional Fe 2+ and H2 O2 " were examined under COD:H2 O2 :Fe 2+ molar ratio of 1:4:1 at pH 2-3 to identify the most effective methods. Identical experiments were conducted for methanol as a reference. Fe 2+ addition methods heavily affected the organics degradation over H2 O2 addition methods. The highest TOC and nitrogen reductions were obtained by "continuous Fe 2+ " addition. Higher concentration of Fe 2+ during "continuous Fe 2+ " addition was detected over other methods, indicating the effective progressing of Fenton reaction. Fractional and continuous addition methods achieved higher organics degradations over conventional method except for the "continuous H2 O2 " addition. Our findings on the effects of reagents addition methods will assist on enhancing Fenton oxidation performances in future studies.